Injury and immune response: applying the danger theory to mosquitoes - Moreno-García, Miguel; Recio-Tótoro, Benito; Claudio-Piedras, Fabiola; Lanz-Mendoza, Humberto (Frontiers in Plant Science, 2014)
The insect immune response can be activated by the recognition of both non-self and molecular by-products of tissue damage. Since pathogens and tissue damage usually arise at the same time during infection, the specific mechanisms of the immune response to microorganisms and to tissue damage have not been unraveled. Consequently, some aspects of damage caused by microorganisms in vector-borne arthropods have been neglected. We herein reassess the Anopheles-Plasmodium interaction, incorporating Matzinger’s danger/damage hypothesis and George Salt’s injury assumptions. The invasive forms of the parasite cross the peritrophic matrix and midgut epithelia to reach the basal lamina and differentiate into an oocyst. The sporozoites produced in the oocyst are released into the haemolymph, and from there enter the salivary gland. During parasite development, wounds to midgut tissue and the basement membrane are produced. We describe the response of the different compartments where the parasite interacts with the mosquito. In the midgut, the response includes the expression of antimicrobial peptides, production of reactive oxygen species and possible activation of midgut regenerative cells. In the basal membrane, wound repair mainly involves the production of molecules and the recruitment of haemocytes. We discuss the susceptibility to damage in tissues, and how the place and degree of damage may influence the differential response and the expression of damage associated molecular patterns (DAMPs). Knowledge about damage caused by parasites may lead to a deeper understanding of the relevance of tissue damage and the immune response it generates, as well as the origins and progression of infection in this insect-parasite interaction.